(untitled) (Communications in Mathematical Research, 2021)
This paper presents a detailed analysis of finding the periodic solutions for the high order Duffing equation x^(2n) + g(x) = e(t) (n≥1).Firstly, we give a constructive proof for the existence of periodic solutions via the homotopy method. Then we establish an efficient and global convergence method to find periodic solutions numerically.